Social Behavior Of Online Game Enthusiasts In The Environment State High School 1 South Solok - Aldi Fradana; Erianjoni Erianjoni (Postgraduate School, Universitas Negeri Padang, 2020)
This research is based on science and technology encourage the creation of new discoveries in the field of technology, one example of technological findings, namely smartphone. Based on the development of these technologies, the researcher is interesting to conduct a social behavior study of online game enthusiasts in the South Solok 1 High School environment. The theory used in this research is the Differential Association Theory. The results of this study revealed thatstudents are fans of online games in the school environment because students are not cared for in their family environment, are in the wrong environment, and have free habits that come from outside the school environment.